2004
DOI: 10.1111/j.1365-2141.2004.05060.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequencies of chromosomal aberrations in multiple myeloma and monoclonal gammopathy of undetermined significance in direct chromosome preparation

Abstract: SummaryAlthough many cases of multiple myeloma (MM) and monoclonal gammopathy of undetermined significance (MGUS) are cytogenetically normal, interphase fluorescence in situ hybridization (FISH) analyses reveal aberrations in the majority of the cases. Most likely, non-neoplastic cells are more prone to divide in culture than neoplastic cells. Direct chromosome preparations (DCP) would be one way to circumvent this methodological problem. We have investigated 47 bone marrow samples from 39 patients by DCP. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…1,9,16,17,[20][21][22][23][24][25] In this study, we used multiple myeloma (MM) as a model cancer to evaluate the molecular mechanisms of acquisition of genetic instability and progression of cancer because significant chromosomal instability is observed in this malignancy, with more than 11 cytogenetic abnormalities observed per karyotype and with demonstrated progressive cytogenetic change over time in patient samples and in myeloma-derived cell lines. [26][27][28] Here we report that HR activity is constitutively elevated in MM cell lines and patient samples and demonstrate that the inhibition of HR activity leads to a significant reduction in the acquisition of new genetic changes whereas induction of HR activity leads to significant elevation in the number of new mutations over time and development of drug resistance in MM cells. [29][30][31][32] and were maintained in a state of logarithmic growth.…”
mentioning
confidence: 94%
“…1,9,16,17,[20][21][22][23][24][25] In this study, we used multiple myeloma (MM) as a model cancer to evaluate the molecular mechanisms of acquisition of genetic instability and progression of cancer because significant chromosomal instability is observed in this malignancy, with more than 11 cytogenetic abnormalities observed per karyotype and with demonstrated progressive cytogenetic change over time in patient samples and in myeloma-derived cell lines. [26][27][28] Here we report that HR activity is constitutively elevated in MM cell lines and patient samples and demonstrate that the inhibition of HR activity leads to a significant reduction in the acquisition of new genetic changes whereas induction of HR activity leads to significant elevation in the number of new mutations over time and development of drug resistance in MM cells. [29][30][31][32] and were maintained in a state of logarithmic growth.…”
mentioning
confidence: 94%
“…Several studies have suggested that IgH translocations might occur early in the development of monoclonal gammopathies, possibly as an immortalizing event, rather than related to transition to MM (9 -11, 18, 20 -22). There is still matter of debate whether D13 is an initiation event or is related to transition to MM due to the variable percentage of MGUS patients displaying that anomaly in literature data (9, 10, 18 -23 Thus far, little is known about the real incidence of hyperdiploidy and hypodiploidy in MGUS due to inability to do conventional cytogenetic study in most instances (14,15). Flow cytometry (FCM), a good method to ascertain hyperdiploidy in MM patients (24 -27), was applied to MGUS patients and, although the number of cases reported was low, showed that some patients showed a hyperdiploid PC clone (24 -26, 28, 29).…”
mentioning
confidence: 99%
“…Occurrence of D13 in hypodiploid MGUS might be a late event, possibly related to transition to MM. However, we cannot exclude that hypodiploidy is rare in MGUS because hypodiploid MM originates rarely from a preceding MGUS condition.IgH rearrangements account for up to 70% of MM patients and 50% of MGUS patients (8,9,15,18,20) and have been proposed as the primary event in the process leading to MM (10,11,22,36). Using image cytometry and cIg-FISH, 73% of MGUS patients showed chromosome changes, a percentage higher than that related to IgH translocations.…”
mentioning
confidence: 99%
See 2 more Smart Citations